Stroke prevention as a psychological problem - Bondarenko Nikita Ol. (Psychiatry, Neurology and Medical Psychology, 2022)
The article presents an overview of research into psychological factors of stroke. It was determined that the susceptibility to stroke is formed by the following psychological qualities: high emotionality, anxiety, intrapersonal conflict, tension, reduced stress resistance, difficulties in social and psychological adaptation. Two personality psychotypes (A and B )were noted, to which  increased risk for stroke is attributed:1) extroverts, with a fast pace of reactions and emotional excitability, competitiveness, desire for achievements, conflict and a constant feeling of time pressure, impulsive, egocentric, situationally anxious; 2) introverts, emotionally unbalanced, with a changeable character and a tendency to low mood, anxious and prone to depression, insecure. Based on data analysis, it is emphasized the need to learn effective methods of overcoming stress and reducing anxiety, increasing the level of communicative competence and learning effective methods of overcoming conflicts, mastering methods of emotional self-regulation for stroke prevention. Psychological recommendations are proposed for implementation in the lifestyle of the general public for the prevention of psychosomatic diseases.